Combined use of laboratory X-ray diffraction and microtomography in early age cement hydration. - Cuesta-García, Ana María; Shirani, Shiva; Gómez-de-la-Torre, María de los Ángeles; Santacruz-Cruz, María Isabel; Morales-Cantero, Alejandro; Koufany, Imane; Redondo-Soto, Cinthya; Salcedo, Inés R.; León-Reina, Laura; García-Aranda, Miguel Ángel (My University, 2023)
In situ laboratory X-ray powder diffraction (LXRPD) is widely used for studying cement hydration at early ages. However, this approach has limitations due to the intrinsic characteristics of the main methodologies (flat sample and capillary) and their blindness to the amorphous phases and microstructures. In addition, laboratory X-ray microtomography (μ-CT) is being used for several applications but the accuracy of the obtained results is not established. Here, we present an innovative approach where LXRPD and μ-CT data are taken in the same volume of the same hydrating paste within a thick capillary with time. The results from both techniques should agree, resulting in more reliable information. The methodology developed here is based on capillaries of 2 mm of diameter to minimize self-drying and to have very good powder averaging. In this proof-of-principle investigation, μ-CT data have been collected for a PC-42.5R paste, w/c=0.50, at 12 hours and 1, 3 and 7 days, and for LXRPD at 1, 3 and 7 days. Powder diffraction data have been analysed by the Rietveld method and the results have been verified by mass balance calculations. μ-CT data have been segmented. The results indicate that the developed methodology is accurate. The long-term aim of this research is to be able to monitor the reaction of the amorphous components of widely-used supplementary cementitious materials (SCMs) like the amorphous silica in fly/volcanic ashes or the metakaolin in calcined clays.
Keywords: Cemento; Rayos X - Difracción; Laboratory X-ray diffraction; Microtomography; Cement hydration